O2-S4.04 The cost of expedited partner therapy compared to the cost of standard partner referral for the treatment of chlamydia or gonorrhoea. (10th July 2011) - Gift, T; Kissinger, P; Mohammed, H; Leichliter, J; Hogben, M; Golden, M
Abstract : Background: Partner treatment is an important component of sexually transmitted disease (STD) control. Several randomised controlled trials (RCTs) have compared expedited partner treatment (EPT) to unassisted standard partner referral (SR). All of these trials found that EPT significantly increased partner treatment over SR, and some found that EPT significantly lowered re-infection rates in index patients. Methods: We collected cost data to assess the payer-specific, health care system, and societal-level cost of EPT and SR. We used data on partner treatment and index patient re-infection rates from two RCTs examining EPT and SR for patients diagnosed with chlamydia or gonorrhoea. Additional elements were estimated or drawn from the literature, such as the likelihood of progression to and QALY impact of sequelae. We used a Monte Carlo simulation (10 000 iterations) to assess the impact on cost and effectiveness of varying several variables simultaneously, and calculated threshold values for selected variables at which EPT and SR costs per patient were equal. Sensitivity analyses assessed the impact of varying settings in which EPT might be employed, such as one in which no patient counselling or data entry costs were incurred when employing either EPT or SR. Results: From a health care system or societal perspective, EPT was less costly and treated more partners than SR. From the perspective of an individual payer, EPT was less costly than SR if ≥ 40%–45% of male index patients' female partners or ≥38% of female index patients' male partners received care from the same payer. The Abstract O2-S4.04 figure 1 shows the Monte Carlo results for New Orleans and depicts the relationship between the cost difference between EPT and SR and the proportion of partners of the index patient who receive care from the same payer as the index. Negative values in the figure indicate EPT is less costly per patient. In sensitivity analyses, EPT was less costly than SR from all payer perspectives when counselling and data entry costs were eliminated; when counselling costs were applied to EPT alone, the payer-perspective cost of EPT was greater than SR for index women, but the additional cost was less than 2600 per QALY gained over SR. Conclusions: EPT has a lower cost from a societal or health care system perspective than SR and treats more partners. Individual payers may find EPT to be more costly than SR, depending on how many of their patients' partners receive care from the same payer.